MiR-452 Regulates C2C12 Myoblast Proliferation and Differentiation via Targeting ANGPT1 - Yang, Lingzhi; Qi, Qi; Wang, Jian; Song, Chengchuang; Wang, Yanhong; Chen, Xi; Chen, Hong; Zhang, Chunlei; Hu, Linyong; Fang, Xingtang (Frontiers in Genetics, 2021)
microRNAs are a kind of endogenous, non-coding, single-strand small RNA. They have been reported as an important regulatory factor in skeletal myogenesis. In this study, miR-452 was selected from RNA high-throughput sequencing data to explore its regulatory role in myogenesis. Functionally, miR-452 overexpression could promote C2C12 myoblast proliferation while inhibiting myogenic differentiation. On the contrary, inhibition of miR-452 could suppress C2C12 myoblast proliferation but accelerate myogenic differentiation. Bioinformatics analysis and dual luciferase report assays showed that Angiopoietin 1 (ANGPT1), RB1, and CACNB4 were the potential target genes of miR-452. To further confirm the target relationship between ANGPT1, RB1, and CACNB4 with miR-452, the mRNA level and protein level of these genes were detected by using RT-qPCR and Western blot, respectively. Result analysis indicated that ANGPT1 was a target gene of miR-452. In addition, knockdown of ANGPT1 could obviously promote C2C12 myoblast proliferation but block their differentiation. In summary, these results demonstrated that miR-452 promoted C2C12 myoblast proliferation and inhibited their differentiation via targeting ANGPT1.